2014
DOI: 10.1007/978-1-4939-1658-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry (Fragaria × ananassa)

Abstract: Genetic transformation in strawberry (Fragaria spp.) can be achieved by using the Agrobacterium-mediated procedure on leaves from in vitro proliferated shoots. Regardless of the sufficient regeneration levels achieved from leaf explants of some commercial strawberry genotypes, the regeneration of transformed strawberry plants remains difficult and seems to be strongly genotype dependent. In fact, the main factors that play an important role in the success of strawberry genetic transformation are the availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…4b). So, the efficiency of TDZ in inducing indirect organogenesis observed in strawberry (Landi and Mezzetti 2006;Cappelletti et al, 2015) was also observed in blueberry.…”
Section: Blueberry In Vitro Direct and Indirect Organogenesissupporting
confidence: 55%
See 1 more Smart Citation
“…4b). So, the efficiency of TDZ in inducing indirect organogenesis observed in strawberry (Landi and Mezzetti 2006;Cappelletti et al, 2015) was also observed in blueberry.…”
Section: Blueberry In Vitro Direct and Indirect Organogenesissupporting
confidence: 55%
“…Adventitious shoot regeneration from in vitro cultured explants of cultivated strawberries has been demonstrated for a variety of tissues. Leaf discs remain the most successful and widely used regeneration explant (Nehra et al, 1990;Sorvari et al, 1993;Cappelletti et al, 2015). In addition many other starting tissues have been tested such as: petioles (Focault and Letouze 1987;Rugini and Orlando 1992), stipules (Rugini and Orlando 1992), stem tissues (Graham et al, 1995) runner tissue (Liu and Sanford 1988), the peduncular base of the flower bud (Focault and Letouze 1987), mesophyll protoplast (Nyman and Wallin 1988), anther cultures (Owen and Miller 1996), roots (Rugini and Orlando 1992) and immature embryos (Wang et al, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the widely-used leaf-disk transformation [14,19,20], other tissues are also used for gene transformation21-30. The mature and immature embryo-generated calli are used to develop transgenic plants in rice, maize, wheat and Barley [21][22][23]27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the widely-used leaf-disk infection [14,19,20], other tissues are also used for gene infection [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is previous reported that some factors including suspension Agrobacterium concentrations, Agrobacterium infection time, kanamycin concentration are considerable in plant infection; and the reporter gene is also a good strategy for early infection selection, such as neomycin phosphotransferase gene (NPTⅡ), green fluorescent protein (GFP), red fluorescent protein (DsRed), and β-glucuronidase (GUS) genes [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In addition, the H subunit of magnesium chelatase magnesium chelatase (CHLH), a key enzyme involved in chlorophyll biosynthesis, is chosen as a good reporter gene, in that its silencing phenotype was clearly observed through chimeric phenotypes with yellow/white leaves [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%